Evolving paradigms in prostate cancer screening: a decade of bibliometric insights and technological advancements - Chai, Keqiang; Xu, Changhong; Man, Jiangwei; Deng, Yun; Yang, Li (Frontiers in Oncology, 2025)
ObjectiveProstate cancer is a major threat to global male health. This study uses bibliometric methods to analyze the dynamics and trends in prostate cancer screening research, with the aim of optimizing screening strategies and informing policy decisions.MethodsUtilizing the Web of Science Core Collection database, this study retrieved prostate cancer screening-related literature published between 2014 and 2024, totaling 5,409 articles. Data processing and analysis were conducted using CiteSpace and the Bibliometrix R package, including citation network analysis, co-word analysis, cluster analysis, and trend analysis.ResultsThe analysis revealed the following key findings: (1) Global literature on prostate cancer screening has grown annually, with the United States, Europe, and China leading research activity; (2) Research hotspots include the risks and benefits of prostate-specific antigen (PSA) testing, MRI-based screening technologies, and the use of molecular and genetic biomarkers; (3) Emerging technologies, such as machine learning and nanodiagnostic techniques, are enhancing diagnostic precision and reducing overdiagnosis; (4) Network analysis of collaborations reveals a shift toward transnational and interdisciplinary research, particularly in integrating biomedical and computer science to drive rapid advancements in screening technologies.ConclusionThis study confirms the ongoing vibrancy and technological advancement in the global field of prostate cancer screening research, emphasizing the trend towards precision medicine. Future development of prostate cancer screening strategies should focus on risk-adapted screening and the application of novel biomarkers to optimize screening outcomes and reduce unnecessary medical interventions.